Strategies for maintaining discipline in ELT - Hradecká, Lucie (Univerzita Pardubice, 2011)
The aim of the thesis is to introduce the issue of pupil misbehaviour in connection with the strategies the English teachers may use for maintaining the discipline of learners in ELT lessons. The purpose of the first part of the thesis is to provide theoretical background necessary for the follow-up research. In relation to the issue of maintaining discipline in ELT the theoretical part defines the key words such as social behaviour, classroom discipline and pupil misbehaviour, and describes different psychological approaches towards the modification of social behaviour of learners together with preventative and intervention strategies. The emphasis is laid on the former strategies, in particular, on effective teaching in ELT lessons, which is dealt with in more details in the thesis. The following practical part presents a multi-case study which was aimed at investigating what strategies the English teachers use for dealing with the problem behaviour of learners at a typical basic school. For this purpose, two research tools were utilized, including questionnaires for teachers and observations.
Strategie užívané k udržení kázně při výuce anglického jazyka
Keywords: výuka anglického jazyka; kázeň žáků; nekázeň žáků; preventivní strategie; intervenční strategie; profesní kompetence učitele; efektivní vyučování; English language teaching; ELT; classroom discipline; pupil misbehaviour; preventative strategies; intervention strategies; teacher?s professional competence; effective teaching